Processos de aprendizagem no contexto organizacional da Universidade Federal de Campina Grande - Chagas, Jadelson Rodrigues (2017)
The Federal Institutions of Higher Education have been going through a process of expansion of their campuses, with the need, among others, for the increase of the number of employees in the institutions, and this effective operation is conditioned to the numerous investments of its infrastructure and the training Of its employees as a way to improve the professional and administrative performance of the public sphere. In this perspective, the research analyzes the use of the knowledge obtained by the technical-administrative servers, through the training process offered by the UFCG, being classified as applied, descriptive and qualitative. The empirical field corresponds to Federal University of Campina Grande / Campina Grande Campus. The research subjects, in turn, glimpsed the 34 technical-administrative servers crowded at the Rectory, located in its central campus. The data collection instrument used was the questionnaire, which included open and closed questions about the influence exerted by the knowledge in the execution of the tasks performed in the organizational environment of the Rectory. The method of data analysis was based on the representation of the data by means of graphs and tables for the open and closed questions and for the open questions the content analysis, with the technique of categorization. When analyzing, it is verified that the majority of the servers have an academic formation in the area of Administration and Accounting Sciences, being specialists in Public Management, in Audit and Accounting Sciences. The working time of these servers in the UFCG is from 6 to 10 years, with the majority exercising the positions of Administrator and Accountant. The assignments performed by the servers are diverse, such as: process analysis and evaluation, financial management, sector coordinator and document issuance. Regarding the organizational learning process, it is verified that the majority of the employees have already undergone training courses, mainly in the area of communication, revealing the existence of some type of relation of the course with the position / assignment that they carry out in the UFCG. The perception of the servers in relation to the professional and distance training courses was evaluated in a positive way, being the knowledge used, mainly, in the applications in the work environment. However, most of the servers reveal that there is no change in the execution of the activities, even carrying out the training courses. Of the motivating factors listed by the servers is the functional progression as the main motivation for participation in professional training courses and for the demotivating factors, the main one is the lack of courses in the training area of the technical-administrative server. In addition, the servers reported their opinions about their contribution, through the use of individual learning acquired, through the training courses, with the manifestation of reports regarding the contributions, as well as in disagreement with the organizational learning process. It concludes with the identification of existing gaps in relation to professional training at the Federal University of Campina Grande and, consequently, to the organizational learning process, with the possible solutions to be taken to direct the use of knowledge from the offered training courses in the institution. The Federal Institutions of Higher Education have been going through a process of expansion of their campuses, with the need, among others, for the increase of the number of employees in the institutions, and this effective operation is conditioned to the numerous investments of its infrastructure and the training Of its employees as a way to improve the professional and administrative performance of the public sphere. In this perspective, the research analyzes the use of the knowledge obtained by the technical-administrative servers, through the training process offered by the UFCG, being classified as applied, descriptive and qualitative. The empirical field corresponds to Federal University of Campina Grande / Campina Grande Campus. The research subjects, in turn, glimpsed the 34 technical-administrative servers crowded at the Rectory, located in its central campus. The data collection instrument used was the questionnaire, which included open and closed questions about the influence exerted by the knowledge in the execution of the tasks performed in the organizational environment of the Rectory. The method of data analysis was based on the representation of the data by means of graphs and tables for the open and closed questions and for the open questions the content analysis, with the technique of categorization. When analyzing, it is verified that the majority of the servers have an academic formation in the area of Administration and Accounting Sciences, being specialists in Public Management, in Audit and Accounting Sciences. The working time of these servers in the UFCG is from 6 to 10 years, with the majority exercising the positions of Administrator and Accountant. The assignments performed by the servers are diverse, such as: process analysis and evaluation, financial management, sector coordinator and document issuance. Regarding the organizational learning process, it is verified that the majority of the employees have already undergone training courses, mainly in the area of communication, revealing the existence of some type of relation of the course with the position / assignment that they carry out in the UFCG. The perception of the servers in relation to the professional and distance training courses was evaluated in a positive way, being the knowledge used, mainly, in the applications in the work environment. However, most of the servers reveal that there is no change in the execution of the activities, even carrying out the training courses. Of the motivating factors listed by the servers is the functional progression as the main motivation for participation in professional training courses and for the demotivating factors, the main one is the lack of courses in the training area of the technical-administrative server. In addition, the servers reported their opinions about their contribution, through the use of individual learning acquired, through the training courses, with the manifestation of reports regarding the contributions, as well as in disagreement with the organizational learning process. It concludes with the identification of existing gaps in relation to professional training at the Federal University of Campina Grande and, consequently, to the organizational learning process, with the possible solutions to be taken to direct the use of knowledge from the offered training courses in the institution.